The Inclusive Education for Deaf Children in Primary, Secondary and Preparatory Schools in Gondar, Ethiopia - Tadesse Tedla; Dawit Negassa (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
The purpose of this study was to investigate the current experiences of deaf children in upper primary, secondary and preparatory schools in Gondar City Administration, Ethiopia. A phenomenological study design with qualitative inquiry approach was used. The main tool used for the study was a semi-structured interview guide, which was developed out of comprehensive review of literature for data collection. Out of the thirty deaf children in the study (26 children from grades 5 to 8 and four children from grades 9 to 12), nine were selected through purposive and available sampling techniques from upper primary, secondary and preparatory schools respectively. The data collected were thematically analyzed though the academic dimension points. Results indicated that the deaf children were not academically included at par with the other students, though they were able to receive support from their peers and were active participants in extra-curricular activities. The deaf children were found suffering from communication barrier, unsuitable and non-varied teaching methodologies and lower expectations on the ability of the deaf children from side of teachers. And, the children were also challenged with the absence of sig language interpreters in their classes and the current text books which they deaf children used to study are lacking the incorporations of adequate pictures. Recommendations such as sign language training for teachers and peers, recruitment of sign language interpreters, acquisition of suitable teaching-learning materials along with adequate training of teachers in using effective and varied methodologies for deaf children have been forwarded.